When running for office runs in the family: Horizontal dynasties, policy, and development in the Philippines - DULAY, Dean C. (Institutional Knowledge at Singapore Management University, 2022)
Political dynasties exist in practically every type of democracy, but take different forms in different places. Yet the types of dynastic structures have remained unexplored. We argue that horizontal dynasties—multiple members from the same political family holding different political offices concurrently—affect policymaking by replacing potential political rivals, who may oppose an incumbent’s policy choices, with a member of the family. But in developing countries, the policy change that accrues from dynastic status may not lead to higher levels of economic development. We test this argument’s implications in the Philippines. Using a close elections regression discontinuity design on a sample of mayors, we show that (i) horizontally dynastic mayors have higher levels of government spending, (ii) direct institutional constraints are the mechanism that drives this core result, and (iii) horizontally dynastic mayors do not lead to higher economic growth economic growth or lower poverty.